2015
DOI: 10.4136/ambi-agua.1427
|View full text |Cite
|
Sign up to set email alerts
|

Análise de tendência em séries históricas de vazão e precipitação: uso de teste estatístico não paramétrico

Abstract: Detecting trends in flow and precipitation series has great importance for the management of water resources and can be accomplished using statistic non-parametric tests. This work evaluated the significance of trends in flow and temporal series of precipitation as well as monthly and annual precipitation trends using Pettitt's test. The study used historical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
0
7
0
6
Order By: Relevance
“…Com a finalidade de proceder o estudo da comparação do valor da EEH entre os pacientes que realizam hemodiálise e diálise peritoneal, foi aplicado o teste de Mann-Whitney. Este é um teste não paramétrico, o qual confere se duas amostras distintas pertencem à mesma população (15) . Foram considerados estatisticamente significantes os valores de p inferiores a 0,05.…”
Section: Métodounclassified
“…Com a finalidade de proceder o estudo da comparação do valor da EEH entre os pacientes que realizam hemodiálise e diálise peritoneal, foi aplicado o teste de Mann-Whitney. Este é um teste não paramétrico, o qual confere se duas amostras distintas pertencem à mesma população (15) . Foram considerados estatisticamente significantes os valores de p inferiores a 0,05.…”
Section: Métodounclassified
“…The authors verified a strong connection in relation to the type of use and withdraw of water resources for the station whose analyzes showed a negative trend in all series. Uliana et al (2015) studied trends in time series of rainfall and flow data for the city of Alegre, in the state of Espirito Santo, Brazil, and found that flow rate in October had increased by 34.2% since 1963. They also detected a tendency of increase in rainfall for the months of August and September, since the years of 1967 and 1964, respectively, and concluded that this trend, among other possible factors, may have influenced the increase of the average flow rate for the month of October.…”
Section: Trend Analysismentioning
confidence: 99%
“…Climatic variability and disorderly use of the soil affect several components of the hydrological cycle, impacting the pattern of time series (Salvadori, 2013;Damázio and Costa, 2014;Tan and Gan, 2015;Agevap, 2016). Statistical tests such as Pettitt and Mann-Kendall can be applied to trend analysis in the time series of meteorological and hydrological variables (Barua et al, 2013;Uliana et al, 2015). The Mann-Kendall test (MK) is recommended by the World Meteorological Organization (WMO) and widely applied (Blain, 2010;Caloiero et al, 2011;Lima et al, 2011;Suhaila et al, 2010;Tao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Pettitt test, also used to verify the stationary of the data, allows, in the case of series that do not present stationery, to identify the period in years of the change occurred. This test is a version of the Mann-Whitney statistic Ut, N, applied to verify if two samples x1, ..., xt and xt + 1, xn belong to the same population, the test statistic Ut, N obtained through Equation 4 (Uliana et al, 2015).…”
Section: Stationary Analysis Of Streamflow and Rain Datasetmentioning
confidence: 99%